Pattern recognition for rapid T2 mapping with Stimulate Echo Compensation - Huang, Chuan (2014)
Indirect echoes (such as stimulated echoes) are a source of signal contamination in a multi-echo spin-echo T(2) quantification, and can lead to T(2) overestimation if a conventional exponential T(2) decay model is assumed. Recently, nonlinear least square fitting of a slice-resolve extended phase graph (SEPG) signal model has been shown to provide accurate T(2) estimates with indirect echo compensation. However, the iterative nonlinear least square fitting is computationally expensive and the T(2) map generation time is long. In this work, we present a pattern recognition T(2) mapping technique based on the SEPG model that can be performed with a single pre-computed dictionary for any arbitrary echo spacing. Almost identical T(2) and B(1) maps were obtained from in vivo data using the proposed technique compared to conventional iterative nonlinear least square fitting, while the computation time was reduced by more than 14 fold.